Far-field midinfrared superresolution imaging and spectroscopy of single high aspect ratio gold nanowires - Aleshire, Kyle (Proc Natl Acad Sci U S A, 2020)
Limited approaches exist for imaging and recording spectra of individual nanostructures in the midinfrared region. Here we use infrared photothermal heterodyne imaging (IR-PHI) to interrogate single, high aspect ratio Au nanowires (NWs). Spectra recorded between 2,800 and 4,000 cm(−1) for 2.5–3.9-μm-long NWs reveal a series of resonances due to the Fabry–Pérot modes of the NWs. Crucially, IR-PHI images show structure that reflects the spatial distribution of the NW absorption, and allow the resonances to be assigned to the m = 3 and m = 4 Fabry–Pérot modes. This far-field optical measurement has been used to image the mode structure of plasmon resonances in metal nanostructures, and is made possible by the superresolution capabilities of IR-PHI. The linewidths in the NW spectra range from 35 to 75 meV and, in several cases, are significantly below the limiting values predicted by the bulk Au Drude damping parameter. These linewidths imply long dephasing times, and are attributed to reduction in both radiation damping and resistive heating effects in the NWs. Compared to previous imaging studies of NW Fabry–Pérot modes using electron microscopy or near-field optical scanning techniques, IR-PHI experiments are performed under ambient conditions, enabling detailed studies of how the environment affects mid-IR plasmons.